2021
DOI: 10.1002/ptr.7188
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin‐rich fraction from black rice, Oryza sativa L. var. indica “Luem Pua,” bran extract attenuates kidney injury induced by high‐fat diet involving oxidative stress and apoptosis in obese rats

Abstract: Obesity is acknowledged as being a world health problem and increases the risk of several chronic diseases including chronic kidney disease. High‐fat diet consumption and obesity‐related renal disease show a close correlation with increased oxidative stress. Black rice bran extract, (BRE) Oryza sativa L. variety “Luem Pua” contains a high anthocyanin content. This study evaluated the effects of an anthocyanin‐rich fraction from BRE on renal function and oxidative stress in obese rats. Male Wistar rats were fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Decreases in the apoptotic proteins cytochrome c, Bax, and cleaved caspase 3 along with increases in the anti-apoptotic protein Bcl2 in the RS treatment group were found. These data were confirmed by our previous studies that showed the anti-apoptotic effects of the anthocyanin rich fraction from BR bran and riceberry bran extract in gentamicin-induced nephrotoxicity and obese rat models (Arjinajarn et al, 2017;Laorodphun et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Decreases in the apoptotic proteins cytochrome c, Bax, and cleaved caspase 3 along with increases in the anti-apoptotic protein Bcl2 in the RS treatment group were found. These data were confirmed by our previous studies that showed the anti-apoptotic effects of the anthocyanin rich fraction from BR bran and riceberry bran extract in gentamicin-induced nephrotoxicity and obese rat models (Arjinajarn et al, 2017;Laorodphun et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…BR in the variety name of “Luem‐Pua,” is a traditional food for Asian people. It contains many bioactive substances, including anthocyanin, flavonoids, and γ‐Oryzanol, which exhibit beneficial effects on anti‐diabetes, anti‐obesity, anti‐oxidative stress, and anti‐inflammation (Arjinajarn et al, 2017; Laorodphun et al, 2021; Yang et al, 2019). Several previous studies demonstrated the anti‐lipidemic and anti‐adipogenic effects of BR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oryza sativa L., as a rich source of anthocyanin, was investigated in renal function in obese rats. It was observed to show a reduction in renal injury by the attenuation of either oxidative stress, or apoptosis of renal cells [ 157 ].…”
Section: Discussionmentioning
confidence: 99%